2012
DOI: 10.3354/meps09522
|View full text |Cite
|
Sign up to set email alerts
|

Seed addition facilitates eelgrass recovery in a coastal bay system

Abstract: Eleven years of eelgrass Zostera marina seed additions conducted in a coastal bay system where Z. marina had not been reported since 1933 have resulted in rapid Z. marina expansion beyond the initially seeded plots. From 1999 through 2010, 37.8 million viable seeds were added to 369 individual plots ranging in size from 0.01 to 2 ha totaling 125.2 ha in 4 coastal bays. Subsequent expansion from these initial plots to approximately 1700 ha of bay bottom populated with Z. marina through 2010 is attributable to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 55 publications
2
153
0
Order By: Relevance
“…Our genetic analyses indicated that those naturally recruited patches had a relatively low genetic diversity and showed signs of genetic drift, probably due to a small founding population and subsequent inbreeding. Through intervention via seed-based restoration, areal coverage (see Orth et al 2012) has increased, and the resulting genetic diversity was similar to donor meadows . In this case, restoration is less likely than natural recovery to result in populations that exhibit issues such as inbreeding, because restoration involves a large pulsed addition of seeds rather than the small and slow addition of seeds as in natural recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Our genetic analyses indicated that those naturally recruited patches had a relatively low genetic diversity and showed signs of genetic drift, probably due to a small founding population and subsequent inbreeding. Through intervention via seed-based restoration, areal coverage (see Orth et al 2012) has increased, and the resulting genetic diversity was similar to donor meadows . In this case, restoration is less likely than natural recovery to result in populations that exhibit issues such as inbreeding, because restoration involves a large pulsed addition of seeds rather than the small and slow addition of seeds as in natural recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…1). One site, South Bay, is lo cated within a large Z. marina restoration site in 1 sub-basin along the Virginia and Maryland (USA) Delmarva peninsula's coastal bay system (see Orth et al 2012 …”
Section: Study Sitesmentioning
confidence: 99%
“…The use of seeds harvested from multiple parents, rather than adult plants, could offset this genetic bottleneck. The successful re-establishment of Zostera marina into unvegetated coastal bays in the mid-Atlantic region of the United States using seeds from a number of source beds (Orth et al 2012) offered a unique opportunity to test the hypothesis that genetic diversity is not eroded when seeds are used as in restoration. Here we present results from our analysis of genetic diversity from both natural Z. marina beds in Chesapeake Bay, several of which have served as source beds for restoration, and the restored beds in the Virginia coastal bays.…”
Section: Introductionmentioning
confidence: 99%